Characterization and antioxidant activity of a novel polysaccharide from Pholidota chinensis Lindl. (15th March 2016) - Yang, Haihua; Wu, Yongjie; Gan, Chunji; Yue, Tianli; Yuan, Yahong
Highlights: A novel polysaccharide (PP) was isolated from Pholidota chinensis Lindl. PP was composed of α-1, 3 and α-1, 4 linkedd -mannose units. The 2-O- and 3-O-acetyl groups appeared in the structure of PP. PP showed potential antioxidant activity. Abstract: A novel polysaccharide (PP) was isolated and purified from Pholidota chinensis Lindl. The structure of PP was investigated by HPLC, IR, NMR, etc. and the antioxidant activity was evaluated by hydroxyl radical and superoxide anion assay. Results showed Pholidota chinensis Lindl. contained 3.35% (dry weight) of polysaccharides. The salt-out assay was better than sevag assay for removing protein from crude polysaccharides. The intrinsic viscosity of PP was 1.55 dL/g and its average molecular weight was 45, 200 Da. The monosaccharide composition analysis showed that PP consisted of mannose only. Spectroscopy analysis revealed that PP was mainly composed of α-1, 3 and α-1, 4 linkedd -mannose units with some 2-O- and 3-O-acetyl groups. Moreover, PP can scavenge superoxide anion and hydroxyl radical in a dose-dependent manner, suggesting that PP may be a potential nature antioxidant and may contribute to the analgesic activity of Pholidota chinensis Lindl.